Usage and usability of a web-based program for family caregivers of older people in three European countries: a mixed-methods evaluation - Barbabella, Francesco; Poli, Arianna; Hanson, Elizabeth; Andréasson, Frida; Salzmann, Benjamin; Döhner, Hanneli; Papa, Roberta; Efthymiou, Areti; Valenza, Silvia; Pelliccioni, Giuseppe; Lamura, Giovanni (My University, 2018)
InformCare is a European Web platform that supports informal caregivers of older people by providing access to online information and professional and peer support. The aim of this study was to assess the usage and usability of a psychosocial Web-based program carried out in three European countries (Italy, Sweden, and Germany). A mixed-methods sequential explanatory design was adopted, comprising baseline and postintervention assessments, as well as combined thematic content analysis of results and focus group findings. A convenience sample of 118 caregivers was enrolled, of whom 94 used the services offered by the program at least once. The subsamples in the three countries used the platform in different ways, with a predominance of passive strategies (eg, seeking information and reading other people's comments) for Italian caregivers, and more active usage by Swedish and German caregivers. The usability assessment showed that the platform was perceived well by Italian and German caregivers, whereas technical problems affected the Swedish sample's experiences. Focus group data highlighted user satisfaction with the online support and reliability of the environment. Recommendations for practitioners are to ensure digital training for caregivers who have lower confidence in use of the Internet, to involve different healthcare professionals in the provision of professional support, and to adequately manage online community building.
Keywords: Caregivers; Frail elderly; Health education; Internet; Social support